Adult female acne: a new paradigm. (10th January 2013) - Dréno, B.; Layton, A.; Zouboulis, C.C.; López‐Estebaranz, J.L.; Zalewska‐Janowska, A.; Bagatin, E.; Zampeli, V.A.; Yutskovskaya, Y.; Harper, J.C.
Abstract: In the adult female, acne is a chronic condition with a substantial negative psychological, social and emotional impact. Based on time of onset, two subtypes of adult female acne are recognized: 'persistent acne' is a continuation of the disease from adolescence, while 'late‐onset acne' first presents in adulthood. The morphological characteristics of adult female acne are often distinct from adolescent acne. In adults, inflammatory lesions (particularly papules, pustules and nodules) are generally more prominent on the lower chin, jawline and neck, and comedones are more often closed comedones (micro cysts). Adult acne is mainly mild‐to‐moderate in severity and may be refractory to treatment. A holistic approach to acne therapy should be taken in adult females, which combines standard treatments with adjunctive therapy and cosmetic use. A number of factors specific to the adult female influence choice of treatment, including the predisposition of older skin to irritation, a possible slow response to treatment, a high likelihood of good adherence, whether of child‐bearing age, and the psychosocial impact of the disease. Adherence to therapy should be encouraged through further patient education and a simplified regimen that is tailored to suit the individual patient's needs and lifestyle. This article reviews the specific characteristics of adult female acne, and provides recommendations for acne therapy in this patient group.